2012
DOI: 10.1179/1743132811y.0000000025
|View full text |Cite
|
Sign up to set email alerts
|

Special features of subarachnoid hemorrhage of unknown origin: a review of a series of 179 cases

Abstract: PM-SAH imposed with a mild clinical course and an excellent outcome, without severe complications. In contrast to this, NON-PM-SAH has a significant higher rate of dreaded complications and mortality. It is crucial to make an exact diagnosis of PM-SAH, considering CT scanning during the first 24 hours after occurrence of symptoms and the radiological features.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 29 publications
0
9
2
1
Order By: Relevance
“…The overall yield of our study is within the range of past studies examining the yield of repeat DSA in patients with SAH and a negative initial DSA examination (0%-14% 17,18,27,30,31 ), but it is higher than that in the previous study by Agid et al examining the yield of DSA in patients with SAH and a negative initial CTA (4.2%). The difference in overall yield of DSA between our study and that of Agid et al 29 is likely explained by the larger proportion of patients with perimesencephalic SAH in their patient cohort (48.2%) compared with that in our study (20%).…”
Section: Discussioncontrasting
confidence: 40%
See 2 more Smart Citations
“…The overall yield of our study is within the range of past studies examining the yield of repeat DSA in patients with SAH and a negative initial DSA examination (0%-14% 17,18,27,30,31 ), but it is higher than that in the previous study by Agid et al examining the yield of DSA in patients with SAH and a negative initial CTA (4.2%). The difference in overall yield of DSA between our study and that of Agid et al 29 is likely explained by the larger proportion of patients with perimesencephalic SAH in their patient cohort (48.2%) compared with that in our study (20%).…”
Section: Discussioncontrasting
confidence: 40%
“…In our study, a second DSA examination performed 7 days after the initial noninvasive examination yielded positive results only in patients with diffuse SAH (yield of 4.3%), which was similar to that reported by Delgado Almandoz et al 30 (yield of 5.1%) but lower than that reported by Maslehaty et al 31 (yield of 10.8%) in patients with nonperimesencephalic SAH. In both the present study and that of Delgado Almandoz et al, a third DSA examination did not reveal any additional underlying neurovascular abnormalities.…”
Section: Discussioncontrasting
confidence: 38%
See 1 more Smart Citation
“…The differential diagnosis of thunderclap headache remains broad, including aneurysmal and nonaneurysmal causes. 7 Schievink et al have reported the only case within the extensive literature on angiographically negative CSF xanthochromia to include an SRH. 8 With our cases, we add to this singular description by clarifying several points.…”
Section: Discussionmentioning
confidence: 99%
“…8,9,11 None of the reported clinical cases features the combination of an SRH and intraventricular hemorrhage (IVH), although Schievink et al have described a patient with CSF xanthochromia and SRH, suggesting a combination of subarachnoid hemorrhage (SAH) and SRH. 8 Nevertheless, despite extensive cases of idiopathic or angiographically negative SAH and IVH, [2][3][4][5][6][7] the vascular or etiological source of SRH remains unexplained, and the relationship among SAH, IVH, and SRH remains unexamined. Current clinical knowledge regarding patients with SRH is restricted to the aforementioned case report.…”
mentioning
confidence: 99%